Parque-Centro de Memoria, Paz y Reconciliación de San José del Guaviare - Guaviare (2022)
Between the years 1980 to 2016 the department of Guaviare has been the scene of 4307 homicides as a consequence of the internal armed conflict, of which 2340 have been perpetrated in the mu nicipality of San José del Guaviare, showing that it has an unfortunate history to tell of the armed conflict, especially in its cemetery and surroundings, that is why the purpose of this study was to propose a space that serves as a benchmark for the reco very of the memory of the mortal victims of the armed conflict in Colombia and its repair, articulated with the urban space and according to the uses, customs and ideas about death in the cultures present in San José del Guaviare; therefore, a research of mixed approach and descriptive type was carried out, supported by consultation of secondary sources, application of unstructured interviews, and the architect's knowledge of the author. As a result of the study, there is a design of a historical memory center for the reconstruction, in space and time, of the events that took place there, as well as the design of a park with a monument that integrates the memory and reparation of the victims. of the armed conflict, through spaces for participation and recreation that invite the preservation of peace. In addition, the formulation of an alternative redesign of the current San José del Guaviare cemetery.